2013
DOI: 10.1155/2013/564980
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Solitary Fibrous Tumor of the Kidney: Report of the First Case Managed with Interferon

Abstract: Solitary fibrous tumors of the kidney are extremely rare tumors with unpredictable behavior. We describe a case of a patient with a solitary fibrous tumor of kidney with malignant findings with distant metastasis and nephrectomy managed with subcutaneous interferon achieving 23 months of progression-free survival. To date there is no prospective evaluation of any specific modality of treatment, but the surgical management and long-term followup are the only ones so far recommended strategies in the management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 16 publications
0
19
0
3
Order By: Relevance
“…Studies have also demonstrated that preoperative embolization may be employed prior to surgical resection for highly vascular tumors ( 26 , 27 ). Immunotherapy, for example with interferon, may also be effective ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also demonstrated that preoperative embolization may be employed prior to surgical resection for highly vascular tumors ( 26 , 27 ). Immunotherapy, for example with interferon, may also be effective ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…SFT in the kidney is mostly benign but has malignant potential. Recently, there has been an increase in the number of reports of malignant SFT, including metastasis to lymph nodes [ 12 ], lung [ 10 , 13 , 14 ], liver [ 13 , 14 ], pancreas [ 11 ] and bone [ 15 , 16 ], local recurrence [ 17 , 3 ], peritoneal implantation [ 3 ], and invasion to renal vein [ 18 ]. Microscopically, the diagnostic criteria for malignant SFT is the presence of increased cellularity with crowded and overlapping nuclei, pleomorphism, necrosis and hemorrhage, increased mitotic activity more than four mitoses per ten high power fields (HPFs) [ 19 , 8 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microscopically, the diagnostic criteria for malignant SFT is the presence of increased cellularity with crowded and overlapping nuclei, pleomorphism, necrosis and hemorrhage, increased mitotic activity more than four mitoses per ten high power fields (HPFs) [ 19 , 8 , 7 ]. However, some SFT patients without the malignant features in microscopy presented with distant metastasis [ 13 , 14 ] and local invasion [ 18 ], suggesting that non-malignant histology in SFT could not necessarily predict benign behavior and favorable prognosis in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…It is usually found in pleura and pelvis 1 but can also occur in other unusual sites such as central nervous system, orbit, retroperitoneum, maxillary sinus, pancreas, and kidneys. 2 3 4 5 Histologically, they are characterized by proliferation of spindle cells, and immunohistochemically they are positive for CD34. 6 Usually, SFTs are benign in nature, but 10–20% of them are reported to be malignant with a tendency to metastasize.…”
Section: Introductionmentioning
confidence: 99%